Das Organum mathematicum – ein historisches Arbeitsmittel als Quelle für problemorientiertes Arbeiten im zeitgemäßen Mathematikunterricht (mathematica didactica, 2019)
Mathematics education more than 300 years ago - an exciting, diversified enterprise full of fascinating discoveries?! The historic source of the following considerations is the Organum mathematicum by Athanasius Kircher consisting of ten different files on nine different mathematical subjects. The material contained in these files can be the basis for a deep understanding of the mathematical content to be used in class on various age levels. The article deals with some conceptual questions about the use of history of mathematics in the teaching of mathematics using the example of Kircher’s Organum mathematicum. It also discusses the actual use of the historic source in class.